Managing vibration training safety by using knee flexion angle and rating perceived exertion - Chuang, L.-R.; Yang, W.-W.; Chang, P.-L.; Chen, V. C.-F.; Liu, C.; Shiang, T.-Y. (Sensors, 2021)
Whole-body vibration (WBV) is commonly applied in exercise and rehabilitation and its safety issues have been a major concern. Vibration measured using accelerometers can be used to further analyze the vibration transmissibility. Optimal bending angles and rating of perceived exertion (RPE) evaluations have not been sufficiently explored to mitigate the adverse effect. Therefore, the aims of this study were to investigate the effect of various knee flexion angles on the transmissibility to the head and knee, the RPE during WBV exposure, and the link between the transmissibility to the head and the RPE. Sixteen participants randomly performed static squats with knee flexion angles of 90, 110, 130, and 150 degrees on a WBV platform. Three accelerometers were fixed on the head, knee, and center of the vibration platform to provide data of platform-to-head and platform-to-knee transmissibilities. The results showed that the flexion angle of 110 degrees induced the lowest platform-to-head transmissibility and the lowest RPE (p < 0.01). A positive correlation between RPE and the platform-to-head transmissibility was observed. This study concluded that a knee flexion of about 110 degrees is most appropriate for reducing vibration transmissibility. The reported RPE could be used to reflect the vibration impact to the head.